2017
DOI: 10.3762/bjoc.13.257
|View full text |Cite
|
Sign up to set email alerts
|

A semisynthesis of 3'-O-ethyl-5,6-dihydrospinosyn J based on the spinosyn A aglycone

Abstract: Spinetoram, a mixture of 3'-O-ethyl-5,6-dihydrospinosyn J (XDE-175-J, major component) and 3'-O-ethylspinosyn L (XDE-175-L, minor component), is a novel kind of green and efficient insecticide with a broad range of action against various insects. Nowadays, spinetoram is widely used in agriculture and food storage. This work reports a 7-step semisynthesis of 3'-O-ethyl-5,6-dihydrospinosyn J from spinosyn A aglycone. The C9–OH and C17–OH of the aglycone are successively connected to 3-O-ethyl-2,4-di-O-methylrham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…So a chemical synthesis of spinetoram would be helpful for the application of spinetoram, as well as for the further research on spinetoram. In the previous study [ 13 ], we had reported a semi-synthesis of spinetoram J with spinosyn A aglycon as initiator ( Scheme 1 ). However, in the previous route, C9–OH and C17–OH of the aglycone needed to be protected with different protecting groups, resulting in cumbersome steps and high costs.…”
Section: Introductionmentioning
confidence: 99%
“…So a chemical synthesis of spinetoram would be helpful for the application of spinetoram, as well as for the further research on spinetoram. In the previous study [ 13 ], we had reported a semi-synthesis of spinetoram J with spinosyn A aglycon as initiator ( Scheme 1 ). However, in the previous route, C9–OH and C17–OH of the aglycone needed to be protected with different protecting groups, resulting in cumbersome steps and high costs.…”
Section: Introductionmentioning
confidence: 99%